Optimizing the design of invasive placebo interventions in randomized controlled trials. Issue 9 (18th March 2020) - Cousins, S; Blencowe, N S; Tsang, C; Chalmers, K; Mardanpour, A; Carr, A J; Campbell, M K; Cook, J A; Beard, D J; Blazeby, J M
Abstract: Background: Placebo-controlled trials play an important role in the evaluation of healthcare interventions. However, they can be challenging to design and deliver for invasive interventions, including surgery. In-depth understanding of the component parts of the treatment intervention is needed to ascertain what should, and should not, be delivered as part of the placebo. Assessment of risk to patients and strategies to ensure that the placebo effectively mimics the treatment are also required. To date, no guidance exists for the design of invasive placebo interventions. This study aimed to develop a framework to optimize the design and delivery of invasive placebo interventions in RCTs. Methods: A preliminary framework was developed using published literature to: expand the scope of an existing typology, which facilitates the deconstruction of invasive interventions; and identify placebo optimization strategies. The framework was refined after consultation with key stakeholders in surgical trials, consensus methodology and medical ethics. Results: The resulting DITTO framework consists of five stages: deconstruct treatment intervention into constituent components and co-interventions; identify critical surgical element(s); take out the critical element(s); think risk, feasibility and role of placebo in the trial when considering remaining components; and optimize placebo to ensure effective blinding of patients and trial personnel. Conclusion: DITTO considers invasive placebo composition systematically, accounting for risk, feasibility and placebo optimization. Use of the framework can support the design of high-quality RCTs, which are needed to underpin delivery of healthcare interventions. Graphical Abstract: There are challenges in RCTs of invasive interventions with a placebo control. The DITTO framework outlines five stages to optimize invasive placebo design and delivery: deconstruction of the treatment intervention, identification (and removal) of the critical surgical element from the proposed placebo, consideration of risk, feasibility and the role of the placebo in the RCT, and optimization of placebo delivery to ensure effective blinding of patients and trial personnel. DITTO will be useful